(untitled) (Bangladesh Journal of Pharmacology, 2015)
Multienzyme 2-oxoglutarate complex (2-OGDH) together with branched chain ?-ketoacid dehydrogenase (BCKDH) and pyruvate dehydrogenase belong to the family of mitochondrial 2-oxoacid dehydrogenases. Hypolipidemic drugs, bezafibrate and fenofibrate, up-regulate liver BCKDH. The present study has been undertaken to determine the effect of low doses of bezafibrate and fenofibrate on liver 2-OGDH. Fibrates were administrated to rats fed low-protein diet at 5, 10 or 20 mg/kg. In rats treated with increasing doses of bezafibrate 2-OGDH activity increased by 7, 35 and 42%, while in rats administered with fenofibrate by 8, 18, and 56% (p<0.05 for bezafibrate 10 and 20, and fenofibrate 20 mg/kg). Changes in 2-OGDH activity did not correspond with changes in mRNA levels of the complex enzymes. Moreover, mRNA levels of PPAR? remained unaltered. It is conceivable that stimulation of 2-OGDH activity by low doses of fibrates is the result of post-transcriptional events and may have a significant effect on liver metabolism.